DECISION SUPPORT SYSTEM FOR DETERMINATION OF VOCATIONAL SCHOOL DEPARTMENT GKPS-3 PEMATANG SIANTAR USING WEB-BASED WEIGHT PRODUCT METHOD - Lane Ertika Matanari; Arifin Tua Purba; Calen Calen (INFOKUM, 2021)
Following applicable standards throughout Indonesia, prospective vocational students who will register for school will experience major selection (majors). For this reason, prospective students are expected to be able to assess their interests, talents, and abilities so that they do not choose the wrong department to take. The selection of majors for prospective vocational students is the beginning of future career choices, but many prospective students choose majors because of the influence of friends. The role of parents is very important. The direction available at SMK GKPS 3 includes accounting, office administration, and software engineering. The assignment will be adjusted to the student's academic abilities and interests. The purpose of these majors is so that students can be directed in receiving lessons that are following the abilities and talents possessed by students. To assist in the process of determining the direction, a decision support system (SPK) was designed with the Weight Product (WP) method. The WP method is done by using multiplication to relate the attribute rating, where the rating of each attribute must first be ranked with the attribute's weight. Based on the data sample studied, the DSS is designed to operate properly and correctly and is 100% accurate because the results of the comparative evaluation results of manual analysis and the overall analysis of the DSS are appropriate.